Overexpression of the pumpkin (Cucurbita maxima) 16 kDa phloem protein CmPP16 increases tolerance to water deficit - Ramírez-Ortega, Francisco Arturo (Plant Signal Behav, 2014)
The phloem plays an important role in the delivery of nutrients and signals between photosynthetic to heterotrophic tissues. Proteins and RNAs in the phloem translocation stream may have an important role in maintaining the integrity of the sieve tube system, as well as in long-distance signaling. CmPP16 is a pumpkin phloem protein, which has been shown to bind RNA in a non-sequence specific manner, and move it cell-to-cell and conceivably, long-distance. The protein and RNA are found in both companion cell (CC) and sieve elements (SE). However, a more precise function for this protein is not known. In this work we report the overexpression of CmPP16 fused to GFP via transformation of pumpkin (Cucurbita maxima cv. Big Max) plants in the cotyledonary stage by direct inoculation of Agrobacterium tumefaciens and Agrobacterium rhizogenes. Plants overexpressing CmPP16 did not show an obvious phenotype. However, these plants displayed higher photosynthetic capacity during drought than wild-type (WT) pumpkin or transformed with another construct. These results suggest that CmPP16 may be involved in the response to stress through long-distance signaling.